IMPROVING FINANCIAL TRANSPARENCY AND ACCOUNTABILITY OF BUMDES THROUGH A SAVINGS AND LOAN INFORMATION SYSTEM - Mekar Meilisa Amalia; Fithriah Napu; Kraugusteeliana Kraugusteeliana; Nasruddin Khalil Harahap; Muhammad Nordiansyah (Jurnal Ekonomi, 2023)
Improving the financial transparency and accountability of BUMDES via a savings and loan information system is a crucial step in advancing the village economy. In the face of constraints on financial management, financial transparency and accountability are essential components of BUMDES's financial management. This research seeks to analyze financial management issues at BUMDEs so that a savings and loan information system can be developed to assist in overcoming administrative issues such as lengthy processing times and reporting difficulties. The research findings, based on an analysis of user needs, reveal a number of system features, such as managing user data, borrower data, saving and borrowing data, transaction processes, and the ability to generate financial reports in the form of graphs and reports that can aid BUMDEs in the financial management of village funds. The research aims to increase transparency, community participation, and stakeholder confidence in BUMDEs, as well as contribute to the village's sustainable economic development.